2021
DOI: 10.1177/00099228211059666
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Health Beliefs and Practices Among Hispanic Parents

Abstract: Parents’ beliefs about and approaches to their child’s health vary with culture and change within cultures over time. To provide an updated understanding of folk and traditional medicine (FTM) among Hispanic parents in the United States, we surveyed 200 caregivers identifying their child as Hispanic in a pediatric primary care clinic about their cultural health beliefs and practices. Overall, 84% of participants believed in ≥1 folk illness, with foreign-born participants more likely than US-born to endorse fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…This could be for several reasons, including lower income levels that junior enlisted service members receive which could create family financial strain leading to mental distress [ 66 ]. Another reason could be the prevalence of non-traditional medicine beliefs among Hispanic parents and how these beliefs can conflict with western medicine practices [ 67 ]. A recent birth for a Hispanic mother may be particularly stressful, given that she may have to balance health information from her culture and family (which she could have more access to living off post) with that of her practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…This could be for several reasons, including lower income levels that junior enlisted service members receive which could create family financial strain leading to mental distress [ 66 ]. Another reason could be the prevalence of non-traditional medicine beliefs among Hispanic parents and how these beliefs can conflict with western medicine practices [ 67 ]. A recent birth for a Hispanic mother may be particularly stressful, given that she may have to balance health information from her culture and family (which she could have more access to living off post) with that of her practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…Many Mexican Americans incorporate complementary medicine as part of their health care practices, but only a few individuals share this information with their primary physicians and/or other health care providers. Fowler et al [15] studied Hispanic parents' beliefs about and approaches to their child's health. This study provided an updated understanding of folk and traditional medicine (FTM) among Hispanic parents in the United States.…”
Section: Complementary Medicinementioning
confidence: 99%
“…Only 15% of the participants had discussed such folk practices with their child's provider. And 86% of the participants felt comfortable talking to a child's physician [15]. According to Nguyen et al [16], they found that more Mexican Americans patients (range of 66.7 -73.7%) described complementary alternative medicine practitioners as being closer to their cultural traditions than non-Hispanic Whites (11.8%).…”
Section: Complementary Medicinementioning
confidence: 99%